Tanfidz Namudzaj al-Ta’lim Show Not Tell li Tarqiyah Nasyath al-Ta’allum wa Nataij Ta’allum al-Insya’i Laday Muta’allimiy al-Arabiyah fi al-Mustawa al-Mutawassith/Employing the Show Not Tell Teaching Model to Enhance Learning Engagement and Writing Achievement of Intermediate Arabic Learners - Ihwan, Adiaksa; Subari, Masyhudi; Najib, Ahmad Farhan Rif'an; Arif, Nuril Imiawansyam (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
This study aims to overcome the problem of low learning engagement and weak insya’ outcomes among grade 3A students at the Modern Darul Hikmah Islamic Boarding School, Tulungagung, where approximately 70% scored below the Minimum Completeness Criteria with an average score of 65/100, reflecting a monotonous teaching approach. To overcome this issue, the Show Not Tell instructional model was implemented through a Classroom Action Research (CAR) design in two cycles, following the Kemmis and McTaggart framework. Thirty students participated, and data were collected using observation sheets, insya’ tests, questionnaires, and documentation with the assistance of two observers. In Cycle I, student activity averaged only 2.16/4 (53.93%), and the learning success rate was 16.7% (5 of 30 students). After revising the teaching plan, Cycle II showed substantial improvement, with student activity rising to 3.70/4 (92.5%) and all 30 students (100%) achieving success: 63.3% rated “Good,” 26.7% “Very Good,” and 3.3% “Excellent.” These findings highlight the effectiveness of Show Not Tell in fostering active learning and improving writing competence, aligning with previous studies on experiential and active learning. The study concludes that this model significantly enhances motivation, classroom participation, and Arabic writing outcomes, making it a promising approach for Arabic language teaching in pesantren contexts.يهدف هذا البحث إلى معالجة مشكلة انخفاض مستوى التفاعل التعليمي وضعف نتائج الإنشاء لدى طلاب الفصل الثالث A بمعهد دار الحكمة العصري، تولونج أغونج، حيث سجل حوالي 70% من الطلاب درجات أدنى من معيار الحد الأدنى للنجاح بمتوسط 65/100، مما يعكس نهج تدريس رتيب. للتغلب على هذه المشكلة، تم تطبيق نموذج التعليم Show Not Tell من خلال تصميم البحث الإجرائي الفصلي (CAR) في دورتين، وفقًا لإطار عمل كيميس وماك تاغارت. شارك ثلاثون طالبًا، وتم جمع البيانات باستخدام أوراق الملاحظة، واختبارات الإنشاء، والاستبيانات، والتوثيق بمساعدة ملاحظَين. في الدورة الأولى، بلغ متوسط نشاط الطلاب 2.16/4 (53.93%)، وكان معدل نجاح التعلم 16.7% (5 من 30 طالبًا). بعد مراجعة خطة التدريس، أظهرت الدورة الثانية تحسنًا كبيرًا، حيث ارتفع نشاط الطلاب إلى 3.70/4 (92.5%) وحقق جميع الطلاب الثلاثين (100%) النجاح: 63.3% صُنفوا "جيدًا"، و26.7% "جيدًا جدًا"، و3.3% "ممتازًا". تسلط هذه النتائج الضوء على فعالية نموذج Show Not Tell في تعزيز التعلم النشط وتحسين كفاءة الكتابة، بما يتماشى مع الدراسات السابقة حول التعلم التجريبي والنشط. يخلص البحث إلى أن هذا النموذج يعزز بشكل كبير التحفيز، والمشاركة الفصلية، ونتائج الكتابة العربية، مما يجعله نهجًا واعدًا لتدريس اللغة العربية في سياقات المعاهد الإسلامية.